Acute febrile forms of liver fasciolosis - Cuadra, Manuel (1959)
It has presented two cases of acute hepatitis fasciolósica (first cases in Peru). The process of acute character, was characterized by high fever, intense painful hepatomegaly and eosinophilia. In one case could be practiced by laparotomy liver biopsy, the patient being in the fullness of symptoms (probably the first case in the world). Histological examination revealed multiple liver abscess with hepatitis reaction. Cellular infiltration was characterized by very rich in polynuclear eosinophils. In the fragment examined a parasitic element was found. A clinical, etiological, pathological and pathogenic entity of this interesting comment is made. Its relationship with Loeffler syndrome and the Tropical Eosinophilia is analyzed.